FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELENGKAPAN PEMERIKSAAN IBU HAMIL (ANTENATAL CARE) DI PUSKESMAS KOTA ENDE (ANALISIS REKAM MEDIS TAHUN 2017) - Riberu, Fransiska Dominika; Lebuan, Adeline (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2020)
Pregnancy examinations are carried out at least 4 (four) times during the pregnancy period which is carried out 1 (one) time in the first trimester, 1 (One) time in the second trimester, and 2 (Two) times in the third trimester. The purpose of this study was to find out what factors were related to the completeness of antenatal care at the Ende City Health Center. This study uses cross sectional quantitative design with retrospective approach which means using secondary data taken from maternal medical record data that conducted antenatal care visits at Ende City Health Center from January to December 2017. The samples in this study were 103 maternal medical records giving birth who had a pregnancy check up at the Ende City Health Center. The sampling technique is total sampling. The results of this study indicate that there is no relationship between age (p = 0.061), education (p = 0.733), occupation (p = 0.818), parity (p = 0.426) with complete antenatal care (antenatal care). It was concluded that there was no significant relationship between age, education, employment and parity with the completeness of antenatal care. With the results of these studies, the researcher suggests that the next researcher can add other variables and use quantitative and qualitative research methods.